The status of coral reefs and associated reef fishes in Ormoc Bay after the implementation of the fisheries sector program - Villaver, William R. (University o the Philippines in the Visayas-Cebu College, 2006)
A reassessment of the coral reefs in Ormoc Bay was conducted for two months, from April to May 2001. Results showed that 10 years after the implementation of the Fisheries Sector Program, there is no improvement at all in the coralcover of the reefs in Ormoc Bay. The overall live coral of the surveyed areas is still very poor and has even declined from 28% in the 1992 survey to 13% in the present survey. This is attributed primarily to siltation as a consequence of forest denudation and upland erosion, to destructive fishing methods, to low public appreciation regarding coral reef conservation is weak due to political patronage and corruption. The survival of new coral recruits, observed in some sampling sites, is not ensured since light penetration is being greatly affected by the amount of silt coming from the 34 rivers that drain into the bay. The percentage of butterfly fishes (Family Chaetodontidae) in the sampling sites has been reduced from 3.3% of the total fish count in 1992 to 0.8% in the present survey. This substantiate the further degradation of the coral reefs since butterfly fishes (Family Chaetodontidae) are indicators of the health of coral reefs. The percentage of target fishes or commercial fishes in the sampling sites has been reduced from 16% of the total fish count in 1992 to 8% of the total fish count in 2001. This is attributed to high turbidity in some sampling areas, poor coral cover, heavy fishing activities in some areas and weak enforcement of laws regarding illegal fishing. The fisheries in Ormoc Bay is characterized as multi-gear albeit, species specific gear catching fishery exploiting a multi-species stock as a result of a degraded marine coastal habitat. Consequently, fish catch of the fishermen and fisherfolk residents of the coastal communities and upland barangays with Ormoc Bay has also declined. Recommendations to avoid further degradation of coral reefs and further depletion of the fishery resources are discussed.